Anthropometric indices of Orang Asli in Kampung Cangkung, Taman Negara, Kuala Tahan, Pahang - Mohamad Zaidi, Nooriman Soleha; Abdul Samad, Siti Fazlina; Kamaruddin, Harris Kamal; Abu Bakar, Al-Hafiz; Ismail, Zulkifli; Ahmad, Suekori; Ismail, Ahmad Dzulkarnain (Universiti Teknologi MARA, Perlis, 2025)
Negrito is the ethnic of the Bateq tribe which are easily identifiable by their facial characteristics of dark-coloured, woolly hair, dark skin, small stature, rounded face, and wide nose. Bateq in Kampung Cangkung, Taman Negara, Kuala Tahan, Pahang, consisted of 35 families. This study aims to describe the anthropometric indices of the Orang Asli Bateq in Kampung Cangkung and aims to examine the correlation between these indices and body fat percentage. The selection criteria studies involved Orang Asli Bateq populations, specifically focusing on body mass index (BMI), waist-hip circumference, biceps, triceps, and body fat. Participants consisted of n=25 Orang Asli individuals from Kampung Cangkung, Taman Negara, Kuala Tahan, Pahang, including n=9 adults and n=16 children. The result for adults indicated significant weight (r = 0.73), hip circumference (r = 0.78), mid-upper arm circumference (MUAC) (r = 0.86), biceps circumference (r = 0.65), and subscapular skinfold thickness (r = 0.69) which are significantly correlated with body fat percentage. For children indicated significant values in these measurements of BMI (r =.817) hip circumference (r =.966), and mid-upper arm circumference (MUAC) (r=0.80), subscapular skinfold thickness (r =.943), weight (r =.786), waist circumference (r =.766), biceps circumference (r =.802), triceps skinfold thickness (r =.801), and height (r =.667). The study concludes that Orang Asli Bateq in Kampung Cangkung, Taman Negara, Kuala Tahan, Pahang has a Lean Body Composition (42.3%, n=11), Very Lean (7.6%, n=1), Fit (15.4%, n=4) and soft (34.6%, n=9).